2019
DOI: 10.1016/j.compositesb.2019.107000
|View full text |Cite
|
Sign up to set email alerts
|

Relations between intralaminar micromechanisms and translaminar fracture behavior of unidirectional FRP supported by experimental micromechanics

Abstract: The translaminar fracture behaviors of partially different unidirectional composite systems, constituted by the same carbon fibers but different (thermoset vs. thermoplastic) matrices, were characterized by means of compact tension fracture tests. The resulting crack resistance curves (R-curves) and fracture surfaces, were studied in detail and found to be rather different between those material systems, in spite of the same reinforcing fibers at similar volume fractions. In the attempt to justify this differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 32 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…It was found that the major characteristics describing the fracture surfaces in the laminates comprised a mixture of the failure mechanisms, ply splitting, fibers bridging, and fiber pull-out. Haldar et al [ 6 ] showed that the fiber bundle pull-out was the process that dissipates the most energy. Furthermore, Souza et al [ 7 ] modified the ASTM E399 test method to account for the orthotropy of the composite materials and specimen geometry effects using a correction function based on a numerical evaluation of the strain energy release rate.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the major characteristics describing the fracture surfaces in the laminates comprised a mixture of the failure mechanisms, ply splitting, fibers bridging, and fiber pull-out. Haldar et al [ 6 ] showed that the fiber bundle pull-out was the process that dissipates the most energy. Furthermore, Souza et al [ 7 ] modified the ASTM E399 test method to account for the orthotropy of the composite materials and specimen geometry effects using a correction function based on a numerical evaluation of the strain energy release rate.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the direction of loading, mode I, mode II, and mode III translaminar fracture or any combination of them may occur in the laminated composites [10]. Most of researchers have studied the translaminar fracture behavior of laminated composites under mode I loading condition [11][12][13][14][15][16]. For example, Underwood and Kortschot [11], Gigliotti and Pinho [12] measured the translaminar fracture toughness (TFT) of the laminated composites reinforced by carbon bers.…”
Section: Introductionmentioning
confidence: 99%
“…These researchers obtained the mode I translaminar fracture toughness of ax/epoxy laminated composites under compressive and tensile loading states. The in uence of matrix type on the translaminar fracture toughness of laminated composites was evaluated by Haldar et al [15]. These researchers used unidirectional carbon bers to reinforce the laminated composites.…”
Section: Introductionmentioning
confidence: 99%